Impact of structural empowerment on organisational performance: 'empowerment - HR' interface. (2018) - Tyagi, Pallavi; Shah, Hardik
Structural empowerment (SE) is defined as a management process under which an employee gets access to organisational decision-making, information and resources. On analysing definition, one can sense that as a close relationship between SE and OP. This research article made an attempt to explore the facets of SE and their impact on OP using mixed-method research. Data from 206 research and development employees (using structured survey) have been collected from a research institute, Translational Health Science and Technology Institute (THSTI), Faridabad (Haryana), India. To determine and identify the impact of SE on organisation performance (OP), seven in-depth interviews have been conducted. The results found that there exists significant positive correlation between structured empowerment facets and OP. It was further found that SE significantly predicts the change in OP. It further suggested different HR interventions to enhance SE and OP.